Pemanfaatan Media Sosial Sebagai Platform Utama Pemasaran Produk UMKM - Ricky Noor Permadi; Maya Retno Sari; Novi Prawitasari (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2022)
Amid the issue of economic uncertainty and the shift in the use of non-renewable natural resources, Micro Small and Medium Enterprises (MSMEs) have become the new flagship of the Indonesian economy. As if not following the flow of technological developments, many the MSME actors do not take advantage of this technology, especially the use of social media. This article aims to describe and analyze the benefits and advantages of marketing through social media. Utilizing social media as the primary platform for marketing MSME products must be done, because social media is a place for marketing products with relatively low costs, even free. The research method used is literature review. Furthermore, this study was conducted with a focus on two analyses. The first is to dig up information about the benefits of using social media to support MSMEs. Second, to find out the role of the government in increasing the use of social media. Therefore, literature review is the right research method chosen to achieve the objectives of this study. The literature analysis process in this research is carried out by collecting data in the form of relevant scientific articles from the google scholar database published between 2015 and 2022. And then, Vosviewer is used to visualize the most important topics in this subject. The data used as analysis material is secondary data collected from various sources (articles published by national and international reputable journals). The results of the study illustrate that there are so many benefits that MSME actors get when they market their products through social media, this also happens in other countries. The role of the Central Government and Regional Government are needed in accelerating MSME actors to be